Rapid transcriptional down-regulation of c-myc expression during cyclic adenosine monophosphate-promoted differentiation of leukemic cells. - Slungaard, A (1987)
Pharmacologic elevation of cyclic AMP (cAMP) promotes growth arrest and differentiation in a variety of transformed mammalian cells, including the HL-60 human promyelocytic leukemia cell line. However, mechanisms underlying this phenomenon are poorly understood. Because cellular oncogenes play a pivotal role in regulating proliferation and differentiation, we examined whether cAMP-promoted differentiation of HL-60 was preceded by a decrease in the expression of c-myc, a cellular oncogene both amplified and constitutively expressed in HL-60. We find that cyclic AMP elevation in HL-60 caused by three different pharmacologic regimens is followed by an abrupt, greater than 90% decrease in steady state c-myc mRNA levels within 3 h, well before detectable changes in proliferation and differentiation. This decrease, which occurs despite protein synthetic blockade, is attributable to transcriptional down-regulation of c-myc and is accompanied by changes in chromatin structure near c-myc promoter sites. Our findings establish that cAMP, a ubiquitous intracellular regulatory messenger previously known only to enhance gene transcriptional activity in higher eukaryotic cells, can also suppress transcription of a cellular oncogene, thereby suggesting a potential mechanism for cAMP-promoted differentiation.